An Input-output Analysis of Sources of Growth and Key Sectors in Malaysia - Kamaruddin, Rohana; Abdul Rashid, Zakariah; Jusoff, Kamaruzaman (2008)
The paper examines the sources of growth and key sectors of Malaysia’s economy over 1978-2000 using a decomposition method and Rasmussen degree of dispersion within the input-output (IO) framework. The model uses three comparable IO tables for 1978, 1991 and 2000 as the main data sources and accounts for output changes from a demand side perspective. The chosen structural decomposition analysis (SDA) based on the comparison between two IO tables, allows us to decompose each sector’s and industry’s output growth. It decomposes output growth of each sector to domestic demand expansion, export demand expansion, import substitution of final goods, import substitution of intermediate goods, and changes in IO coefficients. The analysis by sub periods, 1978-1991 and 1991-2000 show that there was a switch in the role of domestic-demand and export-demand expansion. The constituent factors that contribute positively to change in the period, 1978-1991 are mostly domestic demand expansion (63.35%) and export demand expansion (33.33%). However in the second sub period, 1991-2000, export demand expansion increased by 12.43% and domestic demand expansion decreased to 48.11%. Taking the whole 1978-2000, domestic demand expansion appears to have been the major source of output growth, contributing about 82%, followed by export demand expansion 62%. Combining the source of growth and key sector through backward linkages, the study revealed that most of the sectors induced its supplying production strongly for domestic market.